PENGARUH ZIKIR TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN STROKE AKUT DI RSUP DR.M. DJAMIL PADANG - Hendri Budi; Herwati Herwati (Jurnal Sehat Mandiri, 2021)
70-94% of acute stroke patients have an increase in blood pressure. Relaxation can be done to treat hypertension. Relaxation in Islam uses zikr (remembering Allah SWT). The purpose of this study was to determine the effect of zikr on reducing blood pressure in acute stroke patients. The research design was quasi-experimental, with two group pretest-posttest design with a control group. The experimental group was given the zikr therapy intervention. The sample of the study was acute stroke patients in the Nervous Room of RSUP Dr. M. Djamil Padang. There were 40 samples, 20 people in the experimental group and 20 people in the control group obtained by purposive sampling. Data collection is September to November 2020 by measuring the patient's blood pressure before and after the intervention. The data is processed manually. Analysis of data with non-parametric Mann Whitney test. The results showed that there was no difference between systolic blood pressure before treatment in the intervention group and the control group (p = 0.976), but there was a difference after treatment (p = 0.000). There was no difference between diastolic blood pressure before treatment in the intervention group and the control group, (p = 0.294), but there was a difference after treatment (p = 0.000). The study concludes that zikr therapy can reduce systolic and diastolic blood pressure in acute stroke patient. It is recommended to the head of the Nerve room to apply zikr therapy in acute stroke patients.